Shrinking Budgets, Growing Demands: Neoliberalism and Academic Identity Tension at Regional Public Universities. (February 2018) - Dugas, Daryl; Summers, Kelly H.; Harris, Lindsay N.; Stich, Amy E.
Faculty ( N = 156) at regional public universities (RPUs) in the United States were surveyed for self-reports of their primary academic identity (teacher, researcher) along with alignment of that identity with perceived departmental expectations and how their time is spent. Well-being and job satisfaction were examined as outcome measures of identity and alignment. The results are examined in the context of international concerns about neoliberalism in higher education, particularly with respect to academic identity. Participants were employed by RPUs in Illinois, a state with severe budget challenges, to assess the combined impact of neoliberalism and financial pressures on academic identity at traditionally teaching-focused institutions. Results of MANCOVA and MANOVA analyses suggested that participants who identify as teachers had greater overall well-being and job satisfaction than those who identified as researchers. Greater satisfaction was associated with alignment between identity and how time is spent. Implications and challenges to faculty work and strains on academic identity at RPUs are discussed.